Prevalence of nonalcoholic fatty liver disease in patients with type 2 diabetes mellitus: A meta-analysis. Issue 39 (September 2017) - Dai, Wenjie; Ye, Ling; Liu, Aizhong; Wen, Shi Wu; Deng, Jing; Wu, Xin; Lai, Zhiwei
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is emerging as a public health issue worldwide and is highly prevalent in patients with type 2 diabetes mellitus (T2DM). However, there was a great disparity across studies in the estimated prevalence of NAFLD in T2DM patients. This meta-analysis, therefore, aimed to estimate the pooled prevalence of NAFLD in T2DM patients. Methods: Electronic databases of PubMed, Web of Science, Embase, Chinese National Knowledge Infrastructure, and Wanfang were searched using MeSH terms to identify relevant studies. Eligibility assessment and data extraction were conducted independently by 2 investigators and a meta-analysis was performed to synthesize the data. Heterogeneity was evaluated using the Cochran Q test and quantified using the I 2 statistic. Publication bias was assessed using both the Begg and Egger tests. Subgroup analyses were performed to identify the possible sources of heterogeneity. Results: Twenty-four studies involving 35, 599 T2DM patients were included in this meta-analysis, of which 20, 264 were identified with NAFLD. A high degree of heterogeneity ( I 2 = 99.0%, P < .001) was observed among the eligible studies, with the reported prevalence ranging from 29.6% to 87.1%. The pooled prevalence of NAFLD in T2DM patients, by a random-effects model, was 59.67% (95% confidence interval: 54.31–64.92%). Sensitivity was low and both the Begg test and Egger test showed low possibility of publication bias. Subgroup analyses indicated that the prevalence of NAFLD in T2DM patients differed by gender, obesity, hypertension, dyslipidemia, coronary heart disease, and chronic kidney disease. Conclusions: The high pooled prevalence of NAFLD in T2DM patients found in this study significantly underscores the need for early assessment of NAFLD and the importance of strengthening the management of NAFLD in T2DM patients.